2020
DOI: 10.1136/bmjopen-2020-039798
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally positive: a qualitative study of public perceptions about using health data for artificial intelligence research

Abstract: ObjectivesGiven widespread interest in applying artificial intelligence (AI) to health data to improve patient care and health system efficiency, there is a need to understand the perspectives of the general public regarding the use of health data in AI research.DesignA qualitative study involving six focus groups with members of the public. Participants discussed their views about AI in general, then were asked to share their thoughts about three realistic health AI research scenarios. Data were analysed usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 21 publications
5
71
0
Order By: Relevance
“…This bears out the findings of recent smaller scale studies. 16–18 Women of all ages see human interaction in diagnosis as critical to their experience of high-quality care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bears out the findings of recent smaller scale studies. 16–18 Women of all ages see human interaction in diagnosis as critical to their experience of high-quality care.…”
Section: Discussionmentioning
confidence: 99%
“… 15 A few qualitative studies, although with small sample sizes, have explored public perception of the use of AI in medicine. 16–18 A recent survey conducted in the Netherlands involving 922 participants examined the perception of the use of AI to read mammograms. It found that the women surveyed did not support the use of AI without a human reader.…”
Section: Introductionmentioning
confidence: 99%
“…However, patient and public perceptions regarding health data sharing for AI research are not sufficiently characterized [ 9 ]. Data sharing for AI research purposes is a controversial subject, and therefore, conditional public support for data sharing cannot be assumed to extend to this field of research [ 10 ]. Reasons for this include knowledge and understanding of AI in general [ 10 ], ethical concerns [ 11 ], and fears around the potential reidentification of anonymized personal health data [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data sharing for AI research purposes is a controversial subject, and therefore, conditional public support for data sharing cannot be assumed to extend to this field of research [ 10 ]. Reasons for this include knowledge and understanding of AI in general [ 10 ], ethical concerns [ 11 ], and fears around the potential reidentification of anonymized personal health data [ 12 ]. Furthermore, recent negative media reports about large technology companies using health data for AI research [ 13 ] and several important data breaches and cyberattacks [ 14 ] may undermine public trust in this technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation